2018
DOI: 10.1080/10962247.2018.1425772
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PM2.5 chemical constituents on atmospheric visibility impairment

Abstract: The chemical constituents of PM that majorly effect the visibility impairment are organic matter and elemental carbon, both of which are products of combustion processes. Secondary formations that lead to ammonium sulfate and ammonium nitrate production also impair the visibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 30 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…A surrogate model is a simple model (usually statistical) which can map the inputs to the outputs of the simulation model with sufficiently good accuracy, given the same inputs. In this study, we choose a type of surrogate model called a Gaussian process emulator, which works like a function for multidimensional interpolation and has been used extensively in many areas of applied science (Carslaw et al, 2013;Koehler and Owen, 1996;Queipo et al, 2005;Vanuytrecht and Willems, 2014;Vu et al, 2015;Degroote et al, 2012) and uncertainty assessments of atmospheric models (Lee et al, 2011(Lee et al, , 2012(Lee et al, , 2016. Gaussian process emulators typically require a relatively small number of runs of the computationally expensive model to generate; this is in contrast to other surrogate modelling approaches, such as neural networks, which typically require thousands of model runs to train them.…”
Section: Global Sensitivity Analysis Of Urban Air Pollutionmentioning
confidence: 99%
“…A surrogate model is a simple model (usually statistical) which can map the inputs to the outputs of the simulation model with sufficiently good accuracy, given the same inputs. In this study, we choose a type of surrogate model called a Gaussian process emulator, which works like a function for multidimensional interpolation and has been used extensively in many areas of applied science (Carslaw et al, 2013;Koehler and Owen, 1996;Queipo et al, 2005;Vanuytrecht and Willems, 2014;Vu et al, 2015;Degroote et al, 2012) and uncertainty assessments of atmospheric models (Lee et al, 2011(Lee et al, , 2012(Lee et al, , 2016. Gaussian process emulators typically require a relatively small number of runs of the computationally expensive model to generate; this is in contrast to other surrogate modelling approaches, such as neural networks, which typically require thousands of model runs to train them.…”
Section: Global Sensitivity Analysis Of Urban Air Pollutionmentioning
confidence: 99%
“…However, an average person breathes at a height of 1.5 m above the ground (Kenagy et al, 2016), but little interest has been shown in the particles near the 1.5 m above ground surface. The study on constituent changes in particles is also very important, as the constituent analysis could help to track contributors of PM 2.5 (Khanna et al, 2018). Another reason for clarifying particle constituent is that inhaled particulate matter can have negative effects on respiratory and cardiovascular health, and can even damage DNA (Hong et al, 2002;Lelieveld & Poschl, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This serious air pollution issue not only restricts the sustainable development of the regional economy but also brings negative influences on human health [6]. Particulate matter (PM), a major component of atmospheric pollutants, has received much attention in the field of atmospheric environment research [7][8][9]. There are various sources of PM emission, of which fugitive dust source is one of the most common sources in urban areas [10].…”
Section: Introductionmentioning
confidence: 99%